Historical fiction in the novel The Plight of Venus by Ahmed Khalaf (Journal of the College of Basic Education, 2022)
The study seeks to approach the concept of historical fiction in the novel The Plight of Venus by the Iraqi writer Ahmed Khalaf. Historical fiction, then talking about historical references in the novel, as well as talking about the narrative imagination and the dystopian pattern in it, and ended with some results, including that the relationship between the novel and history is a reciprocal and interactive relationship, and it is a relationship between two spaces (the fictional narrative space and the realistic historical reference space).